'I am sorry for troubling you with the bother of replying! But I really want to know': An unpublished letter by T. E. Lawrence to Max van Berchem about a Mameluke inscription from Naqb (Sinai/Negev). (2nd October 2021) - Munzi, Massimiliano; Sandoz, Corinne
ABSTRACT: Exactly one month before the outbreak of the Great War, on 28 June 1914, Thomas Edward Lawrence hastily wrote a note to the great specialist in Arabic epigraphy, the Swiss scholar Max van Berchem. At that time Lawrence, together with Charles Leonard Woolley, was preparing the publication of The Wilderness of Zin, regarding the archaeological survey of the southern Negev conducted shortly before on behalf of the Palestine Exploration Fund. Discussing the problems of archaeological research at a time when the European powers were seeking to consolidate their strategic positions in the Middle East in view of the impending war, this article touches on the birth of Arabic epigraphy through the epigraphic evidence left by the penultimate Mameluke Sultan, Qansuh al-Ghuri. In particular, the paper provides an update on the inscription from Naqb (Sinai/Negev) referring to the Muslim pilgrimage from Cairo to Mecca, the subject of Lawrence's letter to van Berchem.